Effect of chemical functionalization of multi-walled carbon nanotubes with 3-aminopropyltriethoxysilane on mechanical and morphological properties of epoxy nanocomposites - Kathi, J.; Rhee, K.Y.; Lee, J.H.
Nanocomposites based on epoxy resin and different weight percentages of unmodified, oxidized, and silanized multi-walled carbon nanotubes (MWCNTs)were prepared by cast molding method. Effects of MWCNTs content on the flexural properties were examined. The results showed that as the loading of the MWCNTs increased, improved flexural strength and flexural modulus were observed. The mechanical properties decreased when the MWCNTs content exceeded 0.2 wt.
Keywords: CARBON NANOTUBES; A. POLYMER-MATRIX COMPOSITES (PMCS); B. MECHANICAL PROPERTIES; E. SURFACE TREATMENTS